LED packaging for lighting applications design, manufacturing, and testing - Liu, S. (Sheng), 1963-; Luo, Xiaobing, 1974-; ebrary, Inc.; Chemical Industry Press (Hoboken, N.J. : Wiley, 2011)
"This book provides quantitative methods for optical, thermal, reliability modelling and simulation so that predictive quantitative modelling can be achieved"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Light emitting diodes -- Design and construction; Light emitting diodes -- Computer simulation; Electronic packaging; Electric lighting -- Equipment and supplies; Electronic books